Editorial brain malformation surveillance in the Zika era. Issue 11 (November 2016) - Trevathan, Edwin
Abstract : The current surveillance systems for congenital microcephaly are necessary to monitor the impact of Zika virus (ZIKV) on the developing human brain, as well as the ZIKV prevention efforts. However, these congenital microcephaly surveillance systems are insufficient. Abnormalities of neuronal differentiation, development and migration may occur among infants with normal head circumference who have intrauterine exposure to ZIKV. Therefore, surveillance for congenital microcephaly does not ascertain many of the infants seriously impacted by congenital ZIKV infection. Furthermore, many infants with normal head circumference and with malformations of the brain cortex do not have clinical manifestations of their congenital malformations until several months to many years after birth, when they present with clinical manifestations such as seizures/epilepsy, developmental delays with or without developmental regression, and/or motor impairment. In response to the ZIKV threat, public health surveillance systems must be enhanced to ascertain a wide variety of congenital brain malformations, as well as their clinical manifestations that lead to diagnostic brain imaging. Birth Defects Research (Part A) 106:869–874, 2016. © 2016 The Authors Birth Defects Research Part A: Clinical and Molecular Teratology Published by Wiley Periodicals, Inc.